Mapping expatriate resource gains: The impact of company policy design - Coelho, J. V. (Journal of Global Mobility-The Home of Expatriate Management Research, 2026)
Purpose This study investigates how expatriate willingness emerges as a function of company policy design within Portuguese multinational corporations. While traditional expatriation frameworks often present standardized mobility approaches, this research explores how policy-induced resource dynamics shape employee motivation, engagement and adjustment, especially across heterogeneous global assignments in under-researched contexts. Design/methodology/approach Using conservation of resources (COR) theory as an analytical lens, this qualitative study analyzed five Portuguese multinational firms spanning diverse sectors. Data were gathered through 200 documents and 37 interviews, 13 with HR and senior managers, 24 with expatriates. Interviews were guided by selection criteria emphasizing career stage, international experience, and family situation. Thematic analysis was conducted using MaxQDA, producing 2,961 data segments coded into 61 thematic categories. Findings The study identified three distinct motivational profiles among expatriates: (1) Conformist expatriates, whose engagement was shaped by psychological contracts and a sense of organizational belonging; (2) Protean expatriates, driven by strategic career advancement and a desire for autonomy; and (3) Disrupted expatriates, characterized by defensive compliance and heightened contextual strain. Company policy design emerged as a critical qualifying mechanism, either facilitating broaden-and-build resource spirals or amplifying depletion trajectories. Dynamic, inclusive policies fostered protean motivation by enabling job crafting and providing robust support structures. In contrast, rigid, functionalist policies tended to constrain disrupted profiles, intensifying allostatic load and hindering adjustment. Research limitations/implications Findings are context-specific to Portugal-based firms and rely on interviewee self-report. Longitudinal studies are needed to trace career development and resource flows over time. Future research should also test the proposed typology across cultural and institutional settings to refine applicability. Practical implications HR practitioners can apply the proposed typology to tailor assignment planning. Recommended practices, aimed to enhance expatriate outcomes and reduce assignment failure, include pre-assignment assessments of willingness and resource readiness, typology-sensitive support structures and feedback-rich environments to monitor resource spirals. HR practitioners should embed dynamic capability principles into expatriation workflows (e.g. personalized preparation, context-responsive support, iterative feedback and supervisor coaching), as these practices have demonstrated greater alignment with upward resource spirals. Originality/value This study advances Conservation of Resources (COR) theory by conceptualizing expatriate willingness not as a static trait, but as a negotiated outcome shaped by the organizational resource ecology. It introduces a threefold typology (conformist, protean and disrupted) that captures motivational diversity and illustrates how policy orientation influences psychological contracts and adaptive behavior. The empirical setting of Portuguese multinational corporations operating in transitional economies further extends the geographical scope of global mobility research, offering fresh insight into supply-side readiness and the strategic alignment of mobility policies.